Assessment of the nutrient intake and micronutrient status in the first trimester of pregnant women in Jakarta (Medical Journal of Indonesia, 2017)
Background: Maternal nutrition before and during pregnancy is important for a healthy pregnancy outcome. According to National Basic Health Research (Riskesdas) 2013, 24.2% of pregnant women are at risk of chronic malnutrition and 37.1% of them suffer from anemia. The aim of this study was to obtain information about the nutrient intake and serum micronutrient status in the first trimester of pregnant women in Jakarta.Methods: A descriptive study was conducted towards 234 pregnant women with gestational age no more than 14 weeks. The nutrient intake data was obtained from the conversion of frequency food questionnaire (FFQ) which was semi quantitative data using a Nutrisurvey application. The maternal serum was examined to obtain data about nutrient level.Results: The mean of daily maternal energy intake was 1,256.1 kcal. Most subjects had nutrient intake below the recommendations of Institute of Medicine (IOM) and recommended dietary allowances (RDA), i.e. energy (88.9%), protein (80.8%), iron (85%), folic acid (74.8%), calcium (90.6%), and zinc (94.9%). However, they showed a high intake level of vitamin A (70.5%). Most subjects had deficiency in vitamin A (69.7%), vitamin D (99.6%), and zinc (81.2). No correlation was found between the maternal nutrient intake and nutritional status.Conclusion: Most of the first-trimester-pregnant-women in Jakarta had low maternal energy and nutrient intake, except for vitamin A, as well as low serum vitamin A, vitamin D, and zinc level.